Germination and initial growth of non-conventional species of physalis on different substrates and environments - Cecco, Rafael Machado de; Klosowski, Elcio Silvério; Silva, Daniel Fernandes da; Villa, Fabíola (Revista de Ciências Agroveterinárias, 2018)
The use of substrates and environments is an important factor to be considered in determining the quality of germination and seedling growing of species of physalis. Given the above, the objective with this study was to evaluate the germination and early crowing of two non-conventional species of physalis, subjected to different environments and substrates. Were conducted two simultaneous experiments in the period from March to May / 2014 in Unioeste, PR. The experimental design used in the first experiment was a randomized, 2x3 factorial (2 physalis species: Physalis minima, Physalis ixocarpa x 3 environments: protect environment with plastic cover of 150 µm, greenhouse with 50% of shading and full sun) blocks containing 3 replicates and 50 seeds per experimental plot. The design of the second experiment was randomized, 2x4 factorial (2 physalis species: Physalis minima, Physalis ixocarpa x 4 substrates: expanded vermiculite of medium texture + latossol, Húmus Fértil® + latossol, washed sand of fine texture + latossol and Humus Fértil® + expanded vermiculite of medium texture, in proportion 1:1 v:v) blocks containing three replicates of 32 seeds per experimental plot. Was monitored by 22 days the experiments to obtain the emergence speed index. 60 days after the sowing was evaluated seedling height, stem diameter, number of leaves, fresh and dry biomass of seedlings. We conclude that, agricultural greenhouse and greenhouse of shade net providing emergence speed index of Physalis minima and Physalis Ixocarpa without distinction between these environments. Seedlings of P. ixocarpa should be produced in agricultural greenhouse, using as substrate mix of Humus fértil® commercial substrate + expanded vermiculite or latosol + vermiculite. Seedlings of P. minima must be produced in a mixture of Humus Fértil® + vermiculite under agricultural greenhouse with or under shade net.